Penguatan Daya Saing UMKM Melalui Pemanfaatan Website sebagai Media Promosi dan Branding Produk Skincare - Andarwati, Tiasri; Rachmatika , Tri Harning; Aisyah , Siti; Rahmawati , Sintia; Ainniyah , Ulfa Nurul; Mahfudhotin, Mahfudhotin (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Harika Skin Beauty is an MSME engaged in skincare products that has challenges in marketing and promotion because it still relies on social media and traditional methods. To increase competitiveness and expand market reach, a digital marketing strategy is needed through website creation. This community service activity aims to help Harika Skin Beauty MSME in utilizing digital technology by creating a website as a marketing and promotion media. The method used is Community-Based Research (CBR) with stages of observation, discussion, design, and website implementation. The results of the activity show that the website https://harikaskinbeauty.blogspot.com/ has been successfully created and provides benefits as a digital catalog that makes it easier for customers to access product information, prices, and purchasing methods. The implementation of this website is expected to increase marketing effectiveness and help MSMEs in facing business competition in the digital era.